FINANCIAL ANALYSIS AND ITS DEFINITION - N.B. Shamuratova; V. Alibekova; G. Amalbekova (Academic Journal of Physical and Chemical Sciences, 2019)
This article is devoted to explanation of financial analysis as a concept, including its methodology and all topics related to this problematics. The findings will subsequently be used for the creation of the actual financial analysis of the selected company. Where financial analysis is determined, explains various approaches to this problem, identifies individual users of financial analysis, as well as sources of information for its creation. It also describes the methodology of a specific approach to financial analysis. Thus, the main attention is paid to the explanation and interpretation of all individual indicators and possible procedures in their formation. The article also contains information about the main characteristics of the selected company and industry and gives the reader an idea of how this company works. Based on the presented financial statements for the past five years, the company will be subjected to analysis of all the indicators explained in the methodological part of the article, and based on correctly interpreted results, conclusions and potential recommendations will be presented. For this purpose, part of the indicators used in financial analysis will be compared with the average values in the industry in which the company operates. This will provide a wider range in which this particular analysis can be used.